Tumour stiffness associated with tumour response to conventional transarterial chemoembolisation for hepatocellular carcinoma: preliminary findings. Issue 10 (October 2019) - Chen, R.; Kong, W.; Gan, Y.; Ge, N.; Chen, Y.; Ding, H.; Luo, J.; Wang, W.; Ren, Z.
Abstract : AIM: To evaluate whether elastic (stiffness) characteristics of tumours were associated with treatment responses and survival of patients with hepatocellular carcinoma (HCC) treated with transarterial chemoembolisation (TACE). MATERIALS AND METHODS: A retrospective cohort study of 59 HCC patients with unresectable HCC who underwent TACE was undertaken. Acoustic radiation force impulse imaging (ARFI) was used to measure tissue stiffness of the index tumours and non-tumoural liver before TACE treatment. The correlation between the parameters of tumour stiffness and treatment response to TACE was assessed using mRECIST criteria as well as according to patient survival. RESULTS: Tumour stiffness and its stiffness difference between tumour and non-tumoural liver were significantly associated with tumour response to TACE ( p= 0.019 and 0.010, respectively). Patients with tumour stiffness of <2 m/s or stiffness difference between tumour and non-tumoural liver of <0.5 were more likely to have treatment response to TACE. Univariate analysis showed that the difference in stiffness between tumour and non-tumoural livers ( p= 0.039) was one of the significant predictors of overall survival (OS). In multivariate analysis, alpha-fetoprotein (AFP) ( p= 0.006) and Barcelona Clinic Liver Cancer (BCLC) stage ( p= 0.017) were identified as independent predictors of survival. CONCLUSION: Tumour stiffness characteristics might be an added predictive marker of treatment response to TACE in patients with HCC. Highlights: Tumor stiffness characteristics associated with tumor response to TACE. Patients with specific tumor stiffness characteristics might be likely to have treatment response to TACE. Tumor stiffness features might be an added predictor of tumor response to TACE.